Pengaruh Kualitas Pelayanan Dan Keamanan, Terhadap Kepuasan Konsumen Pengguna Ojek Online di Bandar Lampung - Ramanda Fichan, M.; Tiara Narundana, Vonny (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
Online motorcycle taxi services have decreased passenger numbers due to lack of service and safety to passengers. This research aims to find out the magnitude of the influence of service quality and consumer safety on the satisfaction of online motorcycle taxi consumers in Bandar Lampung. This type of research is used to analyze data and information obtained from research using descriptive research with a quantitative approach. The sample consisted of 100 onlie motorcycle taxi users in Bandar Lampung. The data is obtained from the koesioner using a likert. The data analysis in this study used multiple linear analysis with the SPSS 25 application. Based on the results of research and data analysis showed that the quality of service and consumer security simultaneously affect consumer satisfaction by 63.3%. The test results of each variable showed that the quality of service significantly affected consumer satisfaction by 61.8% and consumer safety significantly affected consumer satisfaction by 64.1%. by increasing the factors related to online motorcycle taxi companies will increase the satisfaction of online motorcycle taxi users in Bandar Lampung.